SOCIAL SECURITY MANAGEMENT IN THE HEALTH SECTOR IN INDONESIA - Arief Suryono (Faculty of Law, Universitas Sebelas Maret, 2019)
The implementation of social security on health insurance, is a manifestation of Article 28H and 34 of the 1945 Constitution in Indonesia. It is one of the social security guarantees stipulated in Article 19 paragraph (1) of the Law on the National Social Security System provided to participants based on the value of certain contributions or payments on health risks. However, there are differences concerning the obligation of participants on the type of health service to be obtained. Those unable to afford this service are grouped into participants that receive contribution assistance (PBI) paid by the Government. Others include wage recipients (PPU), such as public and private as well as independent employees, including non-wage recipients (PBPU). The existing differences in determining the contribution payment for participants lead to injustice. Therefore, this research aims to analyze the reasons associated with the inability of social justice for health insurance managed by the Healthcare and Social Security Agency (BPJS) to function optimally. The results showed that the functionalization of the social justice principle managed by BPJS requires changes to the provisions of health insurance. It also showed the process used to determine the group of PBPU and BPI participants and the number of contributions by investors and employers.